Pengembangan Media Pembelajaran Teka Teki Silang berbasis Android pada Mata Pelajaran Bahasa Indonesia - Maftakhun, Maftakhun (Attractive : Innovative Education Journal, 2022)
The purpose of this study is to determine the needs, form, and effectiveness of developing android learning media with crossword puzzles, which are carried out by (a) conducting preliminary research, (b) carrying out planning (defining abilities, formulating goals, determining materials and sequence of learning, (c) Develop learning media with gold proshow, (d) Material expert test and media expert test, (e) Small-scale initial and revised field testing, (f) Large-scale and final revision tests, (g) application in learning. This type of research used in this research is Research and Development (R&D). Research and development (R&D) is a research strategy or method. The subjects in this study were all grade IV students at MI SalamsariKeduTemanggung Regency, totaling 20 MI students. The results and objectives of this study were the average pre-test (before using the media) was 71.75, while the average post-test (after using the media) was 83. According to the calculation of the paired t-test test the result was tcount (5,039) >ttable (2,093), it can be concluded that the learning media of crossword puzzles has a significant influence on Indonesian language learning outcomes for Grade IV MI Salamsari students. Increased learning outcomes prove if there are differences between Indonesian learning outcomes before and after using an Android-based learning media using crosswords. Keywords: Development Learning Media, Learning Teka Teki Silang, Learning Based-Android